Paweł Jasienica and Archaeology - Lech, Jacek; Piotrowska, Danuta (Sensus Historiae, 2019)
In November 1949, an article appeared in the Catholic weekly “Tygodnik Powszechny,” published in Kraków, devoted to excavations conducted as part of the Research Programme on the Beginnings of the Polish State. That is how Paweł Jasienica’s (1909–1970) encounters with archaeology began. The outcome was the first collection of articles with literary depictions of archaeological excavations entitled Świt słowiańskiego jutra [“The Dawn of the Slavic Tomorrow”], published in 1952. The book discussed the latest excavations relating to the beginnings of the Slavs and the Polish state, establishing and popularizing the archaeological reportage as one of the categories of journalistic and literary work. It presented Polish archaeology as a politically engaged science, disputing the claims of German archaeology, inspired by the theories of the Berlin prehistorian Prof. G. Kossinna (1858–1931) and his successors, which were aggressively anti-Slavic and anti-Polish, especially during the reign of Hitler and the German occupation of Poland (1939–1945). The measure of the book’s success was its second edition two years later. The authors of the article have presented the controversies discussed by Jasienica against a historical background. Archaeology fascinated the writer. He visited teams in the field, quickly made friends with archaeologists from different generations. He was on friendly terms with the heads of the most important institutions carrying out excavations: Prof. Z. A. Rajewski (1907–1974), director of the State Archaeological Museum in Warsaw and Prof. A. Gieysztor (1916–1999) - a historian, head of the research programme on the beginnings of the Polish state. During this period, Jasienica spent many weeks at various excavation sites; longest in Biskupin. Organizational changes taking place in the scientific community during the Stalinist period (1949–1955) had ideological motivations. Following the example of the Soviet Union, a research discipline called the history of material culture was created in Poland. It combined archaeology with ethnography, and the history of craft and industry; emphasizing research into the development of productive forces in the spirit of historical materialism. The writer tried to present this direction in another collection of archaeological articles, Archeologia na wyrywki [“Bits and Pieces of Archaeology”]. It appeared in 1956 and is less successful than the first book, though the subject is more to blame for this than the author. In 1961, the State Publishing Institute (Państwowy Instytut Wydawniczy - PIW) brought out another, meticulously edited, book by the increasingly popular writer. Słowiański rodowód [“Slavic Origins”] includes the same articles as the earlier work from 1952, but supplemented by new reports devoted to the latest, sensational discoveries in the Świętokrzyskie Mountains (Holy Cross Mountains - Łysa Góra) and in Wiślica, as well as to Bulgarian antiquities. Archaeology also appears on the pages of several other of Jasienica’s books at this time. It occupies an important place in the first chapters of one of his most important works, Polska Piastów [“Poland in the Times of the Piast Dynasty”], published in 1960. The writer completed it in February 1958. Its great success with readers and the more favourable political situation in the Polish People’s Republic after October 1956 meant that the author could devote his next books to the Polish kings, a subject more compatible with his historical training and personalistic view on history. At the time when Marxism dominated in historiography, these books were enormously successful and widely read. Słowiański rodowód remains Jasienica’s last and best book on archaeological themes. Archaeology was also the subject of various articles published by the writer at this time in the press. Only a few are mentioned here.